CARA MEMATIKAN POHON RASAMALA SEBELUM PENEBANGAN DAN PENGARUHNYA TERHADAP SERANGAN KUMBANG AMBROSIA - Paimin Sukartana; Abdurahim Martawijaya (Jurnal Penelitian Hasil Hutan, 1988)
This  experiment was designed  to  find  out  a  proper   method   of  killing  rasamala  trees  (Altingia  excelsa  Noronha) before  felling  to  improve  the value of the wood. The methods  in the testing  include girdling,  singed with  blowtorch  on the girdling  section,   and poisoned   with  5%  sodium  arsenite solution  or triclopyr  483.6 g/l or a mixture  of triclopyr 100 with picloram   50 g/l. The  chemical  methods   was conducted   by pouring  5 ml of each chemical  into each axed part  of about  30 cm  spacing  which  were made  on the base of the tested  trees. Poisoning  with sodium  arsenite  was also done  by brushing  the solution  on   the girdled  areas.  The incidence  of ambrosia beetle attacks was inspected  to study the effect  of  the treatments on  the  susceptibility of  the  tested   trees  to  the  wood  boring  insects  because   this  group  of  the  pests  may  cause severe damage  on  the  newly  dead  trees if improper  treatment   was carried out.  The  experiment  concludes  that :It  seemed  hard  to kill  rasamala trees  by girdling  even  though  the girdled   section  was singed  with  blowtorch.Poisoning   with  5% sodium  arsenite  solution was  effective  if  the chemical  was brushed  on  the  girdled  section. Application  of this method  killed about  80%  of  the tested trees  after six month  period  of treatment.Poisoning  of  rasamala trees  with  483.6 g/l  triclopyr of  a  mixture  of triclopyr 100 with picloram 50 g/l  through  spacing axed  cuts  made on  the  base of  tree  was effective. The  first  formula  killed  about 80%   of  the  trees after six months  to one  year. Application of  the  latter  chemical  showed better  result  because at the  same  treatment  period  this formula killed  more trees,  about  80 - 100% of the tested  samples.In  case of  the  ambrosia  beetle  infestation, the  entire  poisoned   trees  were  more  susceptible   than  that  of the other treatments. Because the most attacks were  mainly concentrated   arround  the  treated  areas,  the  damage  is probably only  meager in economic role.